PENGARUH CARA PEMBERIAN KONSENTRAT-HIJAUAN TERHADAP RESPON FISIOLOGIS DAN PERFORMA SAPI PERANAKAN SIMMENTAL - Ayu Astuti; Erwanto ,; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2015)
The objective of this research was to study the effect of providingforage and concentrate on physiological response and performance of Simental Cross Beef Cattle.  This research was conducted by using Randomized Block Design (RBD) with three treatments and four blocks.  Beef cattle that used are bull of Simental Cross Beef Cattle with the body weight between 280—359 kg.  The treatment of providingforage and two hours late concentrate (P1), providing concentrate and two hours late forage (P2), providing forage together concentrate (P3).  The data in this research is tested by analyzed of variance and continued with Least Significance Difference (LSD).  The result of this research showed that providing forage and concentrate was significant (P<0,05) on the respiration rate,heart rate, body temperature, dry matter intake, average daily gain, and feed conversion ratio.  The providing forage together concentrate (P3) was the best treatment. Keywords:  simmental cross beef cattle, the providing forage and concentrate, physiological response, performance